2014
DOI: 10.1016/j.jconrel.2014.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically active microcarriers associated with thermosensitive hydrogel as a growth factor releasing biomimetic 3D scaffold for cardiac tissue-engineering

Abstract: The challenge of tissue engineering of the infarcted heart is how to improve stem cell engraftment, survival, homing, and differentiation for myocardial repair. We here propose to integrate human adipose-derived stem cells (ADSCs) and pharmacologically active microcarriers (PAMs), a three-dimensional (3D) carrier of cells and growth factors, into an injectable hydrogel (HG), to obtain a system that stimulates the survival and/or differentiation of the grafted cells toward a cardiac phenotype. PAMs are biodegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 74 publications
2
43
0
Order By: Relevance
“…In this study, we elected to investigate rhIGF-1 release because this growth factor has been used in several TERM applications 46, 47, 48, 49, 50, 51 . We note that we have previously found that the affinity of rhIGF-1 is higher for kerateine than keratose, but that the relative affinity of rhIGF-1 is orders of magnitude lower than other growth factors such as recombinant human bone morphogenetic protein 2 (rhBMP-2) 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we elected to investigate rhIGF-1 release because this growth factor has been used in several TERM applications 46, 47, 48, 49, 50, 51 . We note that we have previously found that the affinity of rhIGF-1 is higher for kerateine than keratose, but that the relative affinity of rhIGF-1 is orders of magnitude lower than other growth factors such as recombinant human bone morphogenetic protein 2 (rhBMP-2) 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, sodium chloride reduces the electrostatic repulsive interactions between the charged proteins promoting attractive hydrophobic interactions. In addition, this salt decreases protein solubility with minimal denaturant effect which allows to optimize the amount of protein precipitates (Giteau et al, 2008a;Karam et al, 2014;Penna et al, 2013). Poloxamer 188 was used in order to enhance protein stability and reduce polymer-protein interactions during the encapsulation as described in many studies (Blanco and Alonso, 1998;Kumar et al, 2007;Paillard-Giteau et al, 2010).…”
Section: Protein Precipitation and Encapsulation Into Microparticlesmentioning
confidence: 99%
“…14 The encapsulation of growth factors into microspheres muted the burst release and allowed for a sustained release over 21 days. The release of growth factors from the PLGA microspheres was attributed to the slow degradation of the polymer over time.…”
Section: New Hydrogel Approaches That Improve Controlled Releasementioning
confidence: 99%